ANALISIS PENGUASAAN KOSAKATA BAHASA MANDARIN PADA SISWA KELAS 10 SMK IMMANUEL II SUNGAI RAYA - Felisia Felisia; Tjen Veronica; Suhardi Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Chinese has become the most popular foreign language for people in the world to learn at the moment. As we all know, mastering Chinese vocabulary is one of the hardships in the process of learning Chinese, especially for second-language learners from Latin alphabet countries such as Indonesia. Therefore, the writer decided to conduct research at Immanuel High School. In order to understand the mastery and difficulties of first-year students of Immanuel High School, this paper uses the literature research method and the test research method to conduct research. The test results showed that the student’s mastery of Chinese vocabulary was 84.2%. The accuracy rate of "Vocabulary Usage" was 45.09%. The accuracy rate of "Lexical Synthesis" was 65.44%. The author found that the difficulty of students in mastering Chinese vocabulary is in the sorting part (vocabulary usage part), the difficulty is that most students not only do not understand the overall meaning of the sentence, but also do not understand how to analyze the context of the selected content and the overall vocabulary, andcannot arrange the options for interference, resulting in them not knowing whether the sentences that have been arranged are tight and reasonable. In addition, the difficulty in filling in the blanks (vocabulary synthesis part) is that some students cannot find the keywords when solving the problem and cannot choose the most suitable words to match.